Polysemous Verbs and Modality in Native and Non-Native Argumentative Writing: A Corpus-Based Study - Salazar, Danica; Verdaguer, Isabel (International Journal of English Studies, 2009)
The present study is a corpus-based analysis of a selection of polysemous lexical verbs used to express modality in student argumentative writing. Twenty-three lexical verbs were searched for in three 100,000-word corpora of argumentative essays written in English by American, Filipino and Spanish university students. Concordance lines were examined to determine their use in the three corpora. After presenting the overall results for all verbs studied, more in-depth linguistic analysis was performed on the polysemous verb feel. These analyses revealed that the non-native writers, unlike their native counterparts, had a limited grasp of the full range of meanings of lexical verbs such as feel. It also showed that all student writers under study employed only a restricted range of lexical verbs to convey modal meanings in their writing.